Analysis of a long-term measurement of air pollutants (2007–2011) in North China Plain (NCP); Impact of emission reduction during the Beijing Olympic Games. (September 2016) - Xu, Ruiguang; Tang, Guiqian; Wang, Yuesi; Tie, Xuexi
Abstract: Five years measurements were used to evaluate the effect of emission controls on the changes of air pollutants in Beijing and its surroundings in the NCP during 2008 Olympic Games (2008OG). The major challenge of this study was to filter out the effect of variability of meteorological conditions, when compared the air pollutants during the game to non-game period. We used four-year (2007, 2009–2011) average as the Non-2008OG to smooth the temporal variability caused by meteorological parameters. To study the spatial variability and regional transport, 6 sites (urban, rural, a mega city, a heavy industrial city, and a remote site) were selected. The result showed that the annually meteorological variability was significantly reduced. Such as, in BJ the differences between 2008OG and 5-years averaged values were 2.7% for relative humidity and 0.6% for wind speed. As a result, the anomaly of air pollutants between 2008OG and Non-2008OG can largely attribute to the emission control. The comparison showed that the major pollutants (PM10, PM2.5, NO, NOx ) at the 6 sites in 2008OG were consistently lowered. For example, PM2.5 in BJ decreased from 75 to 45 μg/m 3 (40% reduction). However, the emission controls had minor effect on O3 concentrations (1% reduction). In contrast, the O3 precursor (NOx ) reduced from 19.7 to 13.2 ppb (33% reduction). The in-sensitivity between NOx and O3 suggested that the O3 formation was under VOCs control condition in NCP, showing that strong VOC emission control is needed in order to significantly reduce O3 concentration in the region. Highlights: A long-term of air pollutants from 2007 to 2011 in NCP is analyzed. The effect of emission control during 2008 Olympics (2008OG) is analyzed. The variability of meteorological conditions is filtered out using 4-year averaged data. This study provided evidence that the emission controls successfully avoided the potential haze occurrence in 2008OG. The in-sensitivity between NOx and O3 suggested that the O3 formation was under VOCs control condition.